Pengaruh Leverage, Likuiditas, dan Pertumbuhan Penjualan Terhadap Financial Distress Perusahaan Subsektor Aneka Industri Periode 2020-2023 - Michelle Natalie Susanto; Gatot Nazir Ahmad; Andy Andy (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study analyzes the effect of Leverage (Debt to Asset Ratio/DAR), Liquidity (Current Ratio/CR), and Sales Growth on Financial Distress, with Firm Size as a control variable. Financial distress is proxied by a Negative Net Income within one year. The object of this study is manufacturing companies in the miscellaneous industry subsector listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. The sample consists of 42 companies, with a total of 168 observations, selected using the purposive sampling method. The data used is secondary data from company financial statements, analyzed using panel data regression with the EViews application, and tested using logistic regression. The results show that Leverage (DAR) has no significant effect on Financial Distress, while Liquidity (CR) and Sales Growth have a negative and significant effect on Financial Distress. Additionally, the control variable, Firm Size, also shows a negative effect on Financial Distress. This study is expected to serve as a consideration for company management in managing debt and formulating sales growth strategies to minimize the risk of financial distress. For investors and creditors, the findings of this study can be used as a reference in evaluating a company's financial condition before making funding and investment decisions.